2017
DOI: 10.1111/hex.12544
|View full text |Cite
|
Sign up to set email alerts
|

Women's perspectives on human papillomavirus self‐sampling in the context of the UK cervical screening programme

Abstract: BackgroundTesting for human papillomavirus (HPV) is being incorporated into the cervical screening programme, with the probable future introduction of HPV as a primary test and a possibility of HPV self‐sampling. In anticipation of this development, we sought to inform future policy and practice by identifying potential barriers to HPV self‐sampling.MethodsA cross‐sectional survey of 194 women aged 20‐64 years was conducted. Logistic regression analysis was used to identify determinants of self‐sampling intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 32 publications
(37 reference statements)
0
41
0
Order By: Relevance
“…For some women, home may not be a safe or a private environment. Furthermore, research into women’s perspectives of HPV self‐testing has identified concerns including low confidence in the ability to self‐sample, worries that samples may be lost or contaminated in the post, that HPV tests may be inferior to cytology tests, and fears about a lack of professional input and low confidence in the test result . Here, it is possible that uncertainties around the HPV SSK per se exerted a greater influence on women’s screening decisions than the general process of how self‐sampling is delivered as covered by the DCE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For some women, home may not be a safe or a private environment. Furthermore, research into women’s perspectives of HPV self‐testing has identified concerns including low confidence in the ability to self‐sample, worries that samples may be lost or contaminated in the post, that HPV tests may be inferior to cytology tests, and fears about a lack of professional input and low confidence in the test result . Here, it is possible that uncertainties around the HPV SSK per se exerted a greater influence on women’s screening decisions than the general process of how self‐sampling is delivered as covered by the DCE.…”
Section: Discussionmentioning
confidence: 99%
“…The inconvenience of attending, coupled with the embarrassment of a gynaecological examination, could potentially be overcome by the use of a HPV SSK. Some women, however, have concerns around their competence to perform a home test . To account for these aspects, we included the attribute ‘Location of the test’ with levels ‘GP surgery/clinic’ and ‘Home’.…”
Section: Methodsmentioning
confidence: 99%
“…Despite generally high acceptability of selfcollection, some women expressed concerns of sampling accuracy and a lack of confidence in collecting the sample correctly 30 . Perceptions of low self-efficacy to perform the test can negatively impact women's attitudes towards using selfsampling 31 , underscoring the need for health education as part of an implementation plan. Additional studies conducted in Australia 28 , Denmark 26 , Sweden 32 , and Norway 33 largely recommend the use of self-collected hpv screening to increase participation in screening among under-screened populations.…”
Section: Using Hpv Self-collection To Reach Under-screened Womenmentioning
confidence: 99%
“…Williams et al [28] report that the lack of knowledge related to HPV and self-sampling is a barrier to wanting the test, and Crofts et al [29] and Penaranda et al [30] argue that the number of women who prefer self-sampling increased by educational interventions on CC and self-sampling. Moreover, it is eminently important to explain about self-sampling safely, efficacy, how to use kits, the diagnosis accuracy, and follow up system according to women's life events, with face to face instructing by clinicians, nurses and midwives as well as training from instruction booklets, DVDs, and explanatory leaflets with self-sampling kit for sustainable self-sampling.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of CC excepted of carcinoma insitu (CIS) in 25-29 year old Japanese women was 3.0 (per 100,000 people) in 2016 [3],and the mortality of the women was 0.3 (per 100,000 people) in 2017 [4]. However, the rate of people attending CC screenings, a preventive measure, was 42.4% in 25-69 year old and 26.5% in [20][21][22][23][24][25][26][27][28][29] year old Japanese women in 2016, being markedly lower than those in Western countries, and similar to middle income country rates [5].…”
mentioning
confidence: 99%